Advanced data mining approaches in the assessment of urinary concentrations of bisphenols, chlorophenols, parabens and benzophenones in Brazilian children and their association to DNA damage. (July 2018) - Rocha, Bruno A.; Asimakopoulos, Alexandros G.; Honda, Masato; da Costa, Nattane L.; Barbosa, Rommel M.; Barbosa, Fernando; Kannan, Kurunthachalam
Abstract: Human exposure to endocrine disrupting chemicals (EDCs) has received considerable attention over the last three decades. However, little is known about the influence of co-exposure to multiple EDCs on effect-biomarkers such as oxidative stress in Brazilian children. In this study, concentrations of 40 EDCs were determined in urine samples collected from 300 Brazilian children of ages 6–14 years and data were analyzed by advanced data mining techniques. Oxidative DNA damage was evaluated from the urinary concentrations of 8-hydroxy-2′-deoxyguanosine (8OHDG). Fourteen EDCs, including bisphenol A (BPA), methyl paraben (MeP), ethyl paraben (EtP), propyl paraben (PrP), 3, 4-dihydroxy benzoic acid (3, 4-DHB), methyl-protocatechuic acid (OH-MeP), ethyl-protocatechuic acid (OH-EtP), triclosan (TCS), triclocarban (TCC), 2-hydroxy-4-methoxybenzophenone (BP3), 2, 4-dihydroxybenzophenone (BP1), bisphenol A bis(2, 3-dihydroxypropyl) glycidyl ether (BADGE·2H2 O), 2, 4-dichlorophenol (2, 4-DCP), and 2, 5-dichlorophenol (2, 5-DCP) were found in >50% of the urine samples analyzed. The highest geometric mean concentrations were found for MeP (43.1 ng/mL), PrP (3.12 ng/mL), 3, 4-DHB (42.2 ng/mL), TCS (8.26 ng/mL), BP3 (3.71 ng/mL), and BP1 (4.85 ng/mL), and exposures to most of which were associated with personal care product (PCP) use. Statistically significant associations were found between urinary concentrations of 8OHDG and BPA, MeP, 3, 4-DHB, OH-MeP, OH-EtP, TCS, BP3, 2, 4-DCP, and 2, 5-DCP. After clustering the data on the basis of i) 14 EDCs (exposure levels), ii) demography (age, gender and geographic location), and iii) 8OHDG (effect), two distinct clusters of samples were identified. 8OHDG concentration was the most critical parameter that differentiated the two clusters, followed by OH-EtP. When 8OHDG was removed from the dataset, predictability of exposure variables increased in the order of: OH-EtP > OH-MeP > 3, 4-DHB > BPA > 2, 4-DCP > MeP > TCS > EtP > BP1 > 2, 5-DCP. Our results showed that co-exposure to OH-EtP, OH-MeP, 3, 4-DHB, BPA, 2, 4-DCP, MeP, TCS, EtP, BP1, and 2, 5-DCP was associated with DNA damage in children. This is the first study to report exposure of Brazilian children to a wide range of EDCs and the data mining approach further strengthened our findings of chemical co-exposures and biomarkers of effect. Graphical abstract: Highlights: 40 endocrine disrupting chemicals were measured in children's urine from Brazil. High urinary concentrations of EDCs were associated with personal care products' use. Urinary concentrations of EDCs were influenced by sex, age and geographic region. Co-exposure to BPA, parabens, and dichlorophenols is associated with DNA damage.